Implications of the Effectiveness of Legal Efforts for Asset Recovery in Corruption Criminal Cases with State Financial Losses - Handono, Reza Prasetyo; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. The influence and pressure in law enforcement of corruption cases is one of the obstacles in the recovery of assets resulting from corruption, so that it can cause law enforcement in corruption cases to experience disorientation, in this case law enforcement that is still focused on arresting and imprisoning perpetrators of corruption only, not on the recovery of assets resulting from corruption to the state. Although several corruptors have been processed criminally and have been sentenced to additional penalties for payment of compensation, the assets obtained from corruption have not been significantly returned to the state, so that the state as the owner of assets or public funds remains the party that suffers losses. The aim of this research is to determine and analyze (1) the legal nature of efforts to recover assets from corruption crimes in overcoming state financial losses, (2) the mechanism for asset recovery in corruption cases that cause losses to state finances, (3) the essence of the effectiveness of the law in efforts to recover assets from corruption crimes to overcome state financial losses. The aproach method used in this study is normative juridical. The specifications of this study are descriptive analytical. The data source used is secondary data. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the research and discussion can be concluded: (1) In relation to the regulation of asset return, legally the Indonesian government has issued various regulations that can be used as a basis/foundation in the government's efforts to return state financial losses as a result of corruption. The efforts referred to are regulated in Law No. 31 of 1999 as amended by Law No. 20 of 2001 concerning the Eradication of Corruption. (2) In terms of criminal procedures, efforts to recover the assets of perpetrators of corruption can be carried out in the following ways: asset tracking, asset freezing, asset confiscation, and asset confiscation. (3) It is necessary to be suported by the existence of a Draft Law on Asset Confiscation, this is because the construction of the criminal law system in Indonesia currently does not place confiscation and confiscation of the proceeds and instruments of corruption as an important part of efforts to reduce the level of state losses.